Pengaruh Kondisi Proses Terhadap Yield Dan Kadar Lignin Pulp Pada Fraksionasi Rumput Perimping Dalam Media Asam Formiat - Sherly Oktarizona,; Zulfansyah Zulfansyah; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Perimping grass (Themeda gigantea) is a lignocellulosic biomassa which has not been utilized optimally. Fractionation of perimping grass can be converted into valuable products. The objectives the research is to study the effect of the process condition on pulp yield and lignin content in pulp. The effect of the process conditions were studied by Response Surface Methodology (RSM) using Central Composite Design (CCD). Fractionation of perimping grass performed on a normal boiling point of the solution with a concentration of formic acid (60%, 70% and 80%), the reaction time of 60-180 minutes, solid liquid ratio of 10/1-20/1, 40 grams perimping grass, HCl catalyst 0,1% wt. The result shows that fractionation of perimping grass have yield pulp of 43,91% to 59,23% and lignin pulp 3,26% - 13,92%. The concentration of formic acid and reaction time influence each response significantly.Keywords: central composite design, formic acid, fractionation of biomass, perimping grass, response surface methodology